Interpretation of selected modified diets by the medical team and in-patients at the Cardinal Santos Memorial Hospital - Cardino, Maria Imelda G. Quintero-
Fifty-four physicians, seven nutritionist-dietitian, and forty-three in-patients at the Cardinal Santos Memorial Hospital participated in a survey on the interpretation of low salt, low fat, and low protein diets. The primary objective of the study was to find out whether the repondents agreed on the quantitative intepretation of selected modified diets (amounts of sodium, fat, and protein allowed for each diet) and qualitative interpretation of each diet (food items allowed or restricted for each diet). Data were obtained through the use of a questionnaire. Results showed that the members of the medical team differed significantly in their interpretation of the amount of nutrient allowed in each of the diets. Significant differences were found also among the four groups of respondents in tewrms of foods allowed or restricted ...
Thesis (Master of Science in Foods and Nutrition) -- University of the Philippines
Keywords: Diet; Nutrition